The Wilson-Garnjobst heterokaryon incompatibility tester strains of Neurospora crassa contain modifiers which influence growth rate of heterokaryons and distort segregation ratios. - D. J. Jacobson; J. Ohrnberger; R. A. Akins (Fungal Genetics Reports, 1995)
Recent interest and accelerated research into the genetics of heterokaryon incompatibility (HI) in Neurospora crassa has led to increased use of the original Wilson-Garnjobst HI tester strains available from FGSC (1994 Catalog of Strains, Part VII.D.1.). We have found inconsistencies and abnormalities in both growth of heterokaryons and segregation of markers in crosses using these strains. First noticed was a lack of vigor and incomplete complementation of markers in forced heterokaryons when compared to compatible heterokaryons with known Oak Ridge (OR) background. Secondly, skewed allele ratios were recorded in crosses between the Wilson-Garnjobst strains and strains with OR background. Perkins and Bjorkman raised a cautionary note about these strains (1978 Neurospora Newsl. 25:24-25), however, they concentrated primarily on the scot mutant present in these and other strains originating from the Rockefeller-Lindegren (RL) background. We have attempted to further characterize the erratic behavior of Wilson-Garnjobst strains and determine if the scot mutant or other modifiers of HI are responsible.